2001
DOI: 10.1099/0022-1317-50-10-902
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Chlamydia trachomatis in fresh tissue specimens from patients with ectopic pregnancy or tubal factor infertility as determined by PCR and in-situ hybridisation

Abstract: The prevalence of chlamydial DNA determined by PCR and in-situ hybridisation (ISH) in fresh tissue specimens (endometrium, fallopian tube and ovary) was investigated in 33 women presenting with ectopic pregnancy (EP), 14 women with tubal factor infertility (TFI) and 50 control patients from the UK and the West Indies. In the UK EP group, chlamydial DNA was detected by PCR in 56% of patients; similar results were found in the Trinidad EP group (67%). In the TFI group, chlamydial DNA was detected in (71%) of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 18 publications
1
37
0
3
Order By: Relevance
“…Similar findings were reported by five previous studies that were unable to detect C. trachomatis DNA in 189 tubal samples collected from EP patients with positive serological markers of C. trachomatis (5,8,19,37,50). In contrast, C. trachomatis DNA was found in 0.03 to 70% of the cases in another five studies (4,15,33,47,70). One explanation for the nondetection of chlamydial DNA in our case group could be the small sample size.…”
Section: Vol 16 2009 Activin and Inos In C Trachomatis-infected Wosupporting
confidence: 89%
See 2 more Smart Citations
“…Similar findings were reported by five previous studies that were unable to detect C. trachomatis DNA in 189 tubal samples collected from EP patients with positive serological markers of C. trachomatis (5,8,19,37,50). In contrast, C. trachomatis DNA was found in 0.03 to 70% of the cases in another five studies (4,15,33,47,70). One explanation for the nondetection of chlamydial DNA in our case group could be the small sample size.…”
Section: Vol 16 2009 Activin and Inos In C Trachomatis-infected Wosupporting
confidence: 89%
“…Nucleic acid amplification tests, which include N-PCR, are more typically used for screening and diagnosing chlamydial infections. The plasmid target DNA is present only in C. trachomatis and at 7 to 10 copies per genome; therefore, targeting it with PCR increases the sensitivity and specificity of the test (4,5,18). We targeted plasmid DNA using N-PCR, but chlamydial DNA was not detected in any of our 14 patients with ectopic pregnancy.…”
Section: Vol 16 2009 Activin and Inos In C Trachomatis-infected Womentioning
confidence: 95%
See 1 more Smart Citation
“…Clinical data suggests that C. trachomatis evades immune-mediated elimination to cause persistent infections in some individuals (4,11,45,54,57,64,68). In women, chronic or recurrent C. trachomatis urogenital infections scar the Fallopian tubes, resulting in infertility and ectopic pregnancies, the two clinically important sequelae of infection (12,13).…”
mentioning
confidence: 99%
“…The finding of chlamydial RNA in Fallopian tube biopsy samples collected from women with ectopic pregnancies suggested that viable, metabolically active bacteria were present in the Fallopian tubes of these women (Gerard et al, 1998). Chlamydial DNA has also been detected in the Fallopian tube tissue collected from women at the time of ectopic pregnancy (Barlow et al, 2001;Noguchi et al, 2002). A report to the contrary regarding the detection of chlamydial DNA in fresh tissue from the Fallopian tubes of women with ectopic pregnancy has, however, also been published and suggested that persistent chlamydial infection of Fallopian tubes was rare in ectopic pregnancy (Bjartling et al, 2007).…”
Section: Ectopic Pregnancy and Chlamydiamentioning
confidence: 99%